2022
DOI: 10.3389/fnbeh.2022.944193
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing or co-designing exercise in healthy adults? Effects on mental health and interoceptive awareness

Abstract: Universal exercise recommendations for adults neglect individual preferences, changing constraints, and their potential impact on associated health benefits. A recent proposal suggests replacing the standardized World Health Organisation (WHO) exercise recommendations for healthy adults by co-designed interventions where individuals participate actively in the decisions about the selected physical activities and the effort regulation. This study contrasts the effects on mental health and interoceptive awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Similarly, a study conducted by Almarcha and colleagues found that participants involved in an exercise regime experienced increased mental health and interoceptive awareness scores. Interoceptive scores increased further for those who were able to co-design their exercise regime [ 39 ]. Finally, in a study assessing the impact of a time management training program on time management and anxiety among nursing undergraduate students, significant improvements were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted by Almarcha and colleagues found that participants involved in an exercise regime experienced increased mental health and interoceptive awareness scores. Interoceptive scores increased further for those who were able to co-design their exercise regime [ 39 ]. Finally, in a study assessing the impact of a time management training program on time management and anxiety among nursing undergraduate students, significant improvements were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Interoceptive processes play a critical role in regulating physical exertion during physical activities and sports [43,49]. Previous research has demonstrated that a codesigned exercise intervention can improve interoceptive awareness and mental health in non-athletes [44]. Additionally, a moderate-vigorous physical activity-based intervention can increase cardiac interoceptive accuracy, and individuals with a higher sports background tend to benefit more than those who are physically inactive [47].…”
Section: Discussionmentioning
confidence: 99%
“…Interoception has recently gained recognition in physical activity and sports performance research as a means of improving physical and mental resilience (understood as a cognitive process focused on coping with difficult events and situations and recovering from them) by monitoring one's inner bodily sensations and making appropriate adjustments [43][44][45][46][47][48]. It plays a crucial role in shaping athletes' emotional experiences, decisionmaking processes, and well-being [43,47,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…The present result is consistent with previous studies. Almrcha et al 9 showed that people engaged in co-designed exercise intervention (they decided about the selected physical activities and the effort regulation) scored higher in almost all MAIA scales (except Not Worrying). Also, interoceptive awareness improved in three MAIA scales (Emotional Awareness, Self Regulation, and Body Listening) among war veterans with post-traumatic stress disorder (PTSD) symptoms after participating in a 12-week integrative exercise intervention program 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Interoceptive processes regulate physical exertion in physically active people, enhancing their physical and mental health and overall well-being 8 . Participating in the exercise intervention program can improve interoceptive awareness in healthy adults 9 , 10 , children 11 , and war veterans 12 . Research suggests that participating in sports also has a beneficial effect on interoceptive awareness 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%